2017
DOI: 10.2147/jpr.s143256
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided methotrexate injection for De Quervain disease of the wrist: what lies beyond the horizon?

Abstract: De Quervain disease (DQVD) is one of the most common causes of lateral wrist pain and can lead to significant disability. The current case involves a right-handed, middle-aged, female patient with severe lateral wrist pain due to DQVD. Her pain was not responsive to oral non-steroidal anti-inflammatory drugs, rehabilitation, and repeated corticosteroid injections. Because she refused surgical intervention, we performed ultrasound-guided methotrexate injections (four times). After the injections, dramatic pain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…13 In the present study, the authors demonstrated that ultrasound-guided steroid injections conferred significantly better outcomes over manual injection techniques, both in terms of injection accuracy as assessed by anatomical studies, 14,21,22 and clinical cure rates. 26,[39][40][41][42][43][44][45] In a study directly comparing both approaches, a 91 percent clinical success rate, defined as the avoidance of surgery, was reported for the ultrasound-guided injection group and a 59 percent success rate was reported for the manual injection group. 26 In cadaveric studies assessing injection accuracies, the accuracy of manual injection techniques targeting the first dorsal compartment ranged from 40 to 100 percent, whereas that of ultrasound-guided injections ranged from 90 to 100 percent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 In the present study, the authors demonstrated that ultrasound-guided steroid injections conferred significantly better outcomes over manual injection techniques, both in terms of injection accuracy as assessed by anatomical studies, 14,21,22 and clinical cure rates. 26,[39][40][41][42][43][44][45] In a study directly comparing both approaches, a 91 percent clinical success rate, defined as the avoidance of surgery, was reported for the ultrasound-guided injection group and a 59 percent success rate was reported for the manual injection group. 26 In cadaveric studies assessing injection accuracies, the accuracy of manual injection techniques targeting the first dorsal compartment ranged from 40 to 100 percent, whereas that of ultrasound-guided injections ranged from 90 to 100 percent.…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive synthesis of the therapeutic applications of ultrasound was compiled and outcomes compared to the present standard of care, to further guide plastic surgeons in the evidence-based management of this condition. 1–61…”
mentioning
confidence: 99%
“…Ibuprofen (Advil, Motrin) and naproxen are two examples used for pain relief. In severe cases, oralSteroids or local anaesthetic injections into the tendon sheath are quite effectively used 20 . Previous studies have identified the prevalence of De Quervain's tenosynovitis among different occupations and its association with thumb pain.…”
Section: Introductionmentioning
confidence: 99%